2018
DOI: 10.14295/bds.2018.v21i2.1547
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the interaction of resin composite with light for predictable aesthetic results in anterior teeth: A case report

Abstract: <p><strong> </strong>This case report illustrates a conservative technique for reintervention on anterior composite restorations in a young patient with composite veneers. The treatment incorporated the use of photos and digital planning to establish a harmonious smile design. In order to conserve the dental tissues, existing resin composites restorations in maxillary anterior teeth were carefully removed to minimize enamel reduction, followed by a study of color and shade of teeth considerin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 28 publications
(35 reference statements)
0
7
0
2
Order By: Relevance
“…It has been suggested that the effects of these lines on the tooth’s perceived dimensions are due to the labial mesiodistal dimension, 8 which is also referred to as the “virtual width,” 9 10 “apparent tooth width,” 11 “perceived width of tooth,” 12 and “apparent face width.” 13 Some authors have also proposed that the distance between the LTLAs could be used to verify the size and symmetry of homonymous teeth. 14 However, this has not yet been reported.…”
Section: Introductionmentioning
confidence: 85%
“…It has been suggested that the effects of these lines on the tooth’s perceived dimensions are due to the labial mesiodistal dimension, 8 which is also referred to as the “virtual width,” 9 10 “apparent tooth width,” 11 “perceived width of tooth,” 12 and “apparent face width.” 13 Some authors have also proposed that the distance between the LTLAs could be used to verify the size and symmetry of homonymous teeth. 14 However, this has not yet been reported.…”
Section: Introductionmentioning
confidence: 85%
“…Overall, the multidisciplinary treatment plan demonstrates to have greater advantages both for the aesthetics and function of the patient, as well as for the work team. New non-invasive restorative ducts are increasingly used and to be properly executed, they need a thorough design to achieve the desired aesthetic results [22].…”
Section: Discussionmentioning
confidence: 99%
“…A seleção das cores de resina a serem utilizadas procede a moldagem inicial e pode ser realizada por meio da técnica de incrementos de resina polimerizados na face Brazilian Journal of Development, Curitiba, v.7, n.11, p. 109291-109307 nov. 2021 vestibular dos dentes envolvidos. Como referência para as etapas de estratificação da resina, a cor da dentina deve ser polimerizado no terço cervical e a cor do esmalte voltada para o terço mais próximo da borda incisal (SCOTTI et al, 2018).…”
Section: Tratamentosunclassified
“…O polimento e acabamento são etapas fundamentais para o sucesso do tratamento, onde serão removidos os excessos e irregularidades para refinamento dos contornos anatômicos. O polimento confere o brilho e reflexão de luz, promovendo homogeneidade à superfície das facetas (PEREIRA et al, 2020;SCOTTI et al, 2018).…”
Section: Tratamentosunclassified